Breast Cancer Presenting as Paraneoplastic Erythroderma: An Extremely Rare Case - Ioannis Protopsaltis; Aspasia Drossou; Ioannis Katsantonis; Nikolaos Roussos; Kassiani Manoludaki; Miltiadis Arvanitis; Athanasia Papazafiropoulou; Stavros Antonopoulos (Case Reports in Medicine)
The skin may exhibit the first clinical evidence of a systemic disease and may provide the first clues to a diagnosis in malignancies. Erythroderma is defined as generalized redness and scaling and it is a clinical manifestation of a variety of underlying diseases including, rarely, solid tumors. Breast cancer is associated with a variety of skin paraneoplastic manifestations like acanthosis nigricans, erythromelalgia, thrombotic thrombocytopenic purpura, acrokeratosis paraneoplastica, dermatomyositis, systemic sclerosis, and scleroderma. However, in the literature, the correlation of erythroderma with breast cancer is quite infrequent. Here, we describe a case of a 76-year-old woman who presented with a paraneoplastic manifestation of erythroderma due to breast cancer.